Penggunaan Media Pojok Baca Melalui Gerakan Literasi Untuk Meningkatkan Minat Baca Siswa SMP - Identa, Emanda Chelly (Piwulang Jurnal Pendidikan Bahasa Jawa, 2025)
Education plays a very important role in shaping the character of each individual, making them able to interact and communicate well in various environments. One factor that greatly influences the quality of education is students' abilities and interests in literacy activities. The purpose of this study was to analyze the role of reading corners in increasing students' interest in reading at SMP N 1 Gatak in order to support the School Literacy Movement (GLS). Using qualitative descriptive methods and a phenomenological approach was used to understand the experiences of students and teachers related to the use of reading corners. Data were obtained through observation, interviews, and documentation, which were then analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that reading corners were effective in encouraging students to read more, both independently and in scheduled activities in class. This program also plays a role in creating an environment that supports reading habits and improves students' literacy skills. However, challenges such as limited book collections and the influence of technology are obstacles in managing reading corners. However, the application of digital technology and the development of more structured literacy programs can overcome these problems. Therefore, corners have proven to be an effective means of strengthening student literacy and developing a reading culture in schools.